Livelihood Vulnerability Resilience Capacity of the Rural Economy in Nigeria’s Bauchi State - Sadiq, Sanusi Mohammed; Singh, Invinder Paul; Ahmad, Muhammad Makarfi; Umar, Mahmood Bala (Journal of Indonesian Applied Economics, 2024)
Purpose This research explores the livelihood vulnerability resilience capacity of the rural economy in Nigeria's Bauchi state, aiming to inform sustainable livelihood policies in the region. Design/methodology/approach Data from 322 households in Bauchi state was collected using a structured questionnaire and interview schedule, employing a multi-stage random sampling technique. Descriptive and inferential statistics were used to analyze the data. Findings Households with more livelihood assets tend to use adaptive strategies like diversification and intensification, reducing vulnerability. However, food insecurity can mask this adaptive capacity, impacting household resilience and rural economy sustainability. Research limitations/implications The findings are specific to Bauchi state and may not be generalizable to other regions or countries. Originality/value This study sheds light on the resilience capacity of households in Bauchi state, emphasizing the importance of enhancing factors that buffer vulnerability and resilience capacity. The findings suggest that resilience capacity significantly influences food security and sustainable livelihoods in the region, highlighting the need for targeted policy interventions.